Oral and Non-Oral Cholesterol-Lowering Drugs with PCSK9 and Other Biomolecules as Targets: Present Status and Future Prospects - Ajoy Basak (Biomolecules)
The accumulation of high levels of cholesterol associated with low-density lipoprotein (LDL) in the bloodstream is the key risk factor for stroke and cardiovascular diseases. Therefore, reducing the concentration of LDL-cholesterol in the blood and maintaining it at an optimum level are vital especially for hypercholesterolemic individuals and cardiovascular patients. Thus, the study of cholesterol management and regulation in the physiological system has drawn significant attention from researchers across the globe. This led to the discovery of several cholesterol-lowering drugs which have been approved for administration either via oral or non-oral routes. Owing to the high comfort level, reduced or no pain, and fewer side effects with oral administration, more focus has been directed towards the development of oral-based cholesterol-lowering drugs. The other modes of administration such as intravenous or intramuscular injections are complex and sometimes painful and less tolerable. Therefore, there was a significant interest to develop oral drugs targeting PCSK9. In fact, some progress has been accomplished in recent years. This review provides an overview of the existing cholesterol-lowering drugs, and the progress made so far with oral-based PCSK9 drugs for lowering LDL-cholesterol. The review is presented in several sections highlighting the molecular targets, the individual drugs, and the modes of administration, with a focus on the oral route.